2018
DOI: 10.1007/s11356-018-2349-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the electrochemical degradation process of the antibiotic ciprofloxacin using a double-sided β-PbO2 anode in a flow reactor: kinetics, identification of oxidation intermediates and toxicity evaluation

Abstract: The electrochemical degradation of ciprofloxacin-CIP (50 mg L in 0.10 mol L NaSO) was investigated using a double-sided Ti-Pt/β-PbO anode in a filter-press flow reactor, with identification of oxidation intermediates and follow-up of antimicrobial activity against Escherichia coli. The effect of solution pH, flow rate, current density, and temperature on the CIP removal rate was evaluated. All of these parameters did affect the CIP removal performance; thus, optimized electrolysis conditions were further explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The same phenomenon was observed by Klidi and co-workers when high current intensity is applied [53], due to the high rate of generation of hydroxyl radicals. Unreacted hydroxyl radicals form hydrogen peroxide and hydroperoxyl radical, with less oxidation power than •OH, reducing the mineralization efficiency [54]: The solution pH significantly affects the degradation rate (the higher the pH, the greater this rate), as recently demonstrated by the electrochemical degradation of CIP (50 mg L −1 in 0.10 mol L −1 Na 2 SO 4 ) in a filter-press flow reactor, using a double-sided Ti-Pt/β-PbO 2 anode [47]. The higher removal at higher pH was related to the two pK a values presented by CIP: 6.1 (carboxyl group) and 8.7 (nitrogen of the piperazine group).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The same phenomenon was observed by Klidi and co-workers when high current intensity is applied [53], due to the high rate of generation of hydroxyl radicals. Unreacted hydroxyl radicals form hydrogen peroxide and hydroperoxyl radical, with less oxidation power than •OH, reducing the mineralization efficiency [54]: The solution pH significantly affects the degradation rate (the higher the pH, the greater this rate), as recently demonstrated by the electrochemical degradation of CIP (50 mg L −1 in 0.10 mol L −1 Na 2 SO 4 ) in a filter-press flow reactor, using a double-sided Ti-Pt/β-PbO 2 anode [47]. The higher removal at higher pH was related to the two pK a values presented by CIP: 6.1 (carboxyl group) and 8.7 (nitrogen of the piperazine group).…”
Section: Resultsmentioning
confidence: 94%
“…The electrogeneration of hydroxyl radicals is one of the most promising AOPs. CIP (50 mg L −1 in 0.10 mol L −1 Na 2 SO 4 ) disappearance was recently attained in 2 h by a double-sided Ti-Pt/β-PbO 2 anode in a filter-press flow reactor, while 75 % of Total Organic Carbon (TOC) was removed after 5 h [47]. The same antibiotic (30 mg L −1 ) has been completely removed and TOC has been reduced to 30 % by the use of a SnO 2 -Sb/Ti mesh anode in 2 h at 30 mA cm −2 [48].…”
Section: Introductionmentioning
confidence: 99%
“…A flow reactor equipped with a Ti-Pt/β-PbO 2 anode electrode was studied towards the electrochemical removal of 50 mg/L CFX using 0.1 M Na 2 SO 4 as the supporting electrolyte by Wachter et al [57]. Complete CFX removal was achieved after 2 h of treatment, where after 5 h, the TOC removal was equal to 75%.…”
Section: Ciprofloxacin (Cfx)mentioning
confidence: 99%
“…Dividing the electrochemical cell with a membrane improved molecule degradation, degree of mineralization and current efficiency. Wachter et al (2019) reported the degradation of ciprofloxacin‐CIP (50 mg/L in 0.1 M Na 2 SO 4 ) using a double‐sided Ti‐Pt/beta‐PbO 2 anode in a filter‐press flow reactor, while monitoring the antimicrobial activity exemplified by E. coli . The optimal electrolysis conditions were explored at pH 10, flow rate = 6.5 L/min, applied current = 30 mA/cm 2 .…”
Section: Physical Treatmentmentioning
confidence: 99%